(untitled) (Surkhet Journal, 2014)
This paper is especially concerned with impact of participtary learning centre in Gamaudi VDC Dailekh. The‌ main‌ objective‌ of‌ this‌ paper‌ was‌ to‌ find‌ out‌ the‌ impact‌ of‌ PLC‌ activities‌ during‌ two‌ years‌ period.‌ This paper is based on descriptive study design. Primary and secondary source of data were used. It tried to analyze effect of running activities and socio-economic behaviour of community. The study has showed that most of the people were literate by PLC class, 60 percent people have got access in GO’s and Ngo’s agencies and increase the key role in community activities. Thus, they success to increase income activities.